Molecular Characterization of α- and β-Thalassaemia Among Children From 1 to 10 Years of Age in Guangxi, A Multi-Ethnic Region in Southern China - He, Sheng; Li, Dongming; Yi, Shang; Huang, Xiuning; Zhou, Chaofan; Chen, Biyan; Zuo, Yangjin; Lin, Li; Chen, Faqin; Wei, Hongwei (Frontiers in Pediatrics, 2021)
Background: Thalassemia is one of the most common genetic diseases in southern China. Howerver, population in different regions or different population has their own spectrums of thalassemia. To investigate the prevalence and spectrum features of thalassemia among children in Guangxi. Hematology and genetic analysis were performed on 71,459 children aged 1 to 10 years in various regions of Guangxi. Results: A total of 11,821 children were diagnoses with thalassemia including 7,615 (10.66%) subjects of α-thalassemia, 3,507 (4.90%) subjects of β-thalassemia and 699 (0.98%) cases with both α- and β-thalassemia. Nine α-thalassemia mutations and 30 genotypes were identified among the α-thalassemia children. The - -SEA and - -SEA /αα were the most frequent mutation and genotype, respectively. One α-thalassemia fusion gene and a rare 2.4kb deletion both causing α+-thalassemia were identified, respectively. Thirteen β-thalassemia mutations and 31 genotypes were characterized among the β-thalassemia children, with the most common mutation CD41-42 (-CTTT) accounting for 46.05% of the β-mutations. Two rare mutations IVS-II-5 (G>C), and IVS-I-2 (T>C) were firstly identified. Furthermore, 92 genotypes were identified among 699 children with both α- and β-thalassemia. Conclusions: Our findings highlight the great heterogeneity and the extensive spectrum of thalassemia among children in Guangxi, which provide an available reference for prevention of thalassemia in this area.